2012
DOI: 10.1590/s1413-81232012000200010
|View full text |Cite
|
Sign up to set email alerts
|

A falta de informação sobre os Organismos Geneticamente Modificados no Brasil

Abstract: A falta de informação sobre os Organismos Geneticamente Modificados no BrasilThe lack of information on Genetically Modified Organisms in BrazilResumo O presente artigo apresenta uma revisão sobre a rotulagem de produtos que apresentem em sua composição Organismos Geneticamente Modificados (OGM), também denominados de transgênicos. São abordadas as convenções, as leis e as normas referentes a esses produtos dispostos no mercado, a adequação dos mesmos às normas vigentes e sua aceitação pela sociedade. Dispõe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
2
0
11
Order By: Relevance
“…(3) specific components that promote nutritional or toxic properties; (4) stability of the inserted gene; (5) nutritional effects associated with specific genetic modification; and (6) any unintended effect that may result from genetic insertion (Camara et al, 2009;Ribeiro;Marin, 2012). Bohn et al (2014), when investigating glyphosatetolerant transgenic soybeans, observed that the crop presented high residues of glyphosate, a broad-spectrum systemic herbicide and desiccant of crops that bind essential amino acids and some minerals, preventing their absorption.…”
Section: Pesticide Heavy Metals and Transgenic Residuesmentioning
confidence: 99%
“…(3) specific components that promote nutritional or toxic properties; (4) stability of the inserted gene; (5) nutritional effects associated with specific genetic modification; and (6) any unintended effect that may result from genetic insertion (Camara et al, 2009;Ribeiro;Marin, 2012). Bohn et al (2014), when investigating glyphosatetolerant transgenic soybeans, observed that the crop presented high residues of glyphosate, a broad-spectrum systemic herbicide and desiccant of crops that bind essential amino acids and some minerals, preventing their absorption.…”
Section: Pesticide Heavy Metals and Transgenic Residuesmentioning
confidence: 99%
“…Na última década do século XX e no início do século XXI vimos no Brasil o surgimento de um embate sobre a liberação dos OGMs (Ribeiro;Marin, 2012) (Santos, 2007). Muitas convenções das quais o Brasil é signatário, resoluções criadas em órgãos públicos e outras instituições, legislações, e diversos instrumentos jurídicos consagram o princípio da pre-…”
Section: Breve Histórico Da Luta Antitransgênicosunclassified
“…Desde meados dos anos 1960, uma nova forma de compreensão da ciência e da tecnologia e suas inter-relações com a sociedade vêm sendo construída. Com isso, a sociedade contemporânea, marcada pela revolução tecnológica, exige da escola o empenho em oportunizar a formação de competências básicas, tanto no exercício da cidadania como no desempenho de atividades profissionais (GOUVÊA; LEAL, 2001;INVERNIZZI;FRAGA, 2007;PINHEIRO et al, 2007a;PINHEIRO et al, 2007b;RICARDO et al, 2007;MARIN, 2012;SCHOR, 2007). Tais atividades profissionais trazem em seu bojo uma miscelânea de conceitos técnocientíficos que necessitam de ampla atualização.…”
Section: Introductionunclassified